Electroacupuncture for post-stroke urinary incontinence: a systematic review and meta-analysis with trial sequential analysis - Jiang, Zefei; Zhi, Na; Liu, Guang; Sun, Xiaoxiang; Chen, Xi; Ma, Dandan; Guo, Mingming; Wang, Siying; Zhang, Hong (Frontiers in Neurology, 2023)
Background The evidence for the effectiveness of electroacupuncture (EA) for post-stroke urinary incontinence (PSUI) patients remains unclear. Therefore, the purpose of this systematic review and meta-analysis was to assess the efficacy of EA for PSUI. Methods and analysis Eight English and Chinese databases were searched from their inception until 1 August 2023 to collect randomized controlled trials (RCTs) that investigated the effect of EA on PSUI. Two reviewers independently selected studies that met the eligibility criteria, extracted the necessary data, and assessed the risk of bias for included studies using Cochrane Handbook version 5.1.0. Meta-analysis was performed using Review Manager software (version 5.4.1). Publication bias detection was conducted using STATA (version 16.0). Sequential analysis was performed using TSA 0.9.5.10 Beta. The Grading of Recommendations Assessment, Development, and Evaluation System (GRADE) was used for assessing the certainty of evidence. Results We included 15 RCTs involving a total of 1,414 patients. The narrative analysis revealed that compared with sham EA, genuine EA exhibited greater efficacy in reducing occurrences of 24-h urinary incontinence while also enhancing maximum cystometric capacity (MCC). Moreover, this effect remained significant even during the 3-month follow-up period. Fourteen studies were encompassed within the quantitative analysis. In contrast to active interventions, EA did not yield an improvement in the responder rate (RR 1.53, 95% CI 0.61 to 3.80, p = 0.36). When compared with basic treatments, the combination of EA with them led to a reduction in 24-h urinary incontinence occurrences (MD −0.56, 95% CI −0.60 to −0.52, p < 0.00001), an improvement in MCC (MD 43.23, 95% CI 28.86 to 57.60, p < 0.00001), and a decrease in residual urine volume (RUV; MD −19.99, 95% CI −29.75 to −10.23, p < 0.0001). However, it did not lead to an increase in the responder rate (RR 1.39, 95% CI 0.88 to 2.20, p = 0.16). In comparison to basic treatments combined with active interventions, the amalgamation of EA and them led to an increase in the responder rate (RR 1.24, 95% CI 1.14 to 1.35, p < 0.00001), a reduction in 24-h urinary incontinence occurrences (MD −2.90, 95% CI −5.26 to −0.55, p = 0.02), a decrease in International Consultation on Incontinence Questionnaire-Short Form scores, and an improvement in both MCC (MD 42.11, 95% CI 23.26 to 60.96, p < 0.0001) and RUV (MD 42.11, 95% CI 23.26 to 60.96, p < 0.0001). Furthermore, all reported adverse effects associated with EA were mild. The trial sequential analysis suggested that a sufficient sample size was available to yield results. However, the level of evidence was predominantly assessed as low or very low. Conclusion Electroacupuncture improved post-stroke urinary incontinence with no serious adverse effects. Caution is warranted due to methodological issues, and more high-quality studies are required to confirm its efficacy and safety. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023449599, Identifier CRD42023449599.